(3UhQI hbajI GdYeGQI GdSdjeGfjI HOeTb EfTGA eMeO LdHi GdefTFs - (3eMeO LdHj GdefTjs
(3ChdgG (B:s
(3QHfG CJfG ai GdOfjG MSfI hai GdCNQI MSfI hbfG YPGH GdfGQ hHYO adGQjH hdG QjHI hGdCeQ dOi eQjg dHjH hdG jPgH Ydi ef JOHQ ai YGde GdeKGd s
(3BNQgG (B:s
(3hhbY GdCTgGO hGdJMQjQ Ydi GdfeW ai Sdc GdJhJQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B23s
(3GdfSNI HgG MhGTs
(3HBNQgG fbhd abg Mfais
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs